Academic major satisfaction scale: psychometric properties and proposal for a measure of academic dropout intention - Lingán-Huamán, Susana K.; Dominguez-Lara, Sergio; Postillos, Indira Orbegoso; Medina, Rosmery Matysek; Esteban, Renzo Felipe Carranza (Frontiers in Education, 2025)
IntroductionThis study aimed to translate and analyze the psychometric properties of the Academic Major Satisfaction Scale in the context of assessing academic dropout intention among Peruvian university students. Shifting the focus of the AMSS scale will provide significant practical value to institutions, as measuring dropout intention will yield directly applicable insights to address student dropout and enhance retention.MethodsAn instrumental, cross-sectional research was carried out with 443 Peruvian university students, 56.2% of whom were women aged between 18 and 25 years (Mage = 20.7; SDage = 2.08).ResultsThe factor analysis confirmed the satisfactory one-dimensional structure of four items, omitting items 5 and 6 (CFI = 1.000; RMSEA = 0.029, CI90% 0.000, 0.103; SRMR = 0.007). Factor loadings fluctuate between 0.64 and 0.91, and reliability was found to be adequate (α = 0.80; ω = 0.883). In addition, evidence of factorial invariance according to sex and academic cycle is reported. Regarding the evidence of validity by association with other variables, acceptable associations were found with self-efficacy, satisfaction with studies, and engagement, which are consistent with the current literature.ConclusionThe new measure introduced in this study, known as the Academic Dropout Intention Scale (ADIS), is a brief scale that presents adequate psychometric properties and is useful for assessing academic dropout intention among Peruvian university students.